2022
DOI: 10.3389/fpubh.2022.782620
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Parental Knowledge About Child Feeding: Evaluation of the Effect of Public Health Policy Communication Media in France

Abstract: BackgroundUnhealthy eating behaviors are risk factors for non-communicable diseases. Parents largely influence the development of eating behaviors during childhood through their feeding practices. Parental feeding practices in line with recommendations are more likely to turn into healthier outcomes in children. From a public health perspective, it should be first ascertained whether providing parents with recommendations about child feeding is a useful approach for increase parental knowledge. Recently, the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…36 Recent studies underline the need for public health communications to disseminate and explain this change in the guidelines to parents and professionals who work with children. 37,38 The very large sample and the collection of detailed sociodemographic and economic data ensure the presence of more statistical power and a favorable level of control over potential confounders. As in most observational studies, the selection/attrition bias was quite important, but the weighted analyses suggest that this bias had a limited impact on our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Recent studies underline the need for public health communications to disseminate and explain this change in the guidelines to parents and professionals who work with children. 37,38 The very large sample and the collection of detailed sociodemographic and economic data ensure the presence of more statistical power and a favorable level of control over potential confounders. As in most observational studies, the selection/attrition bias was quite important, but the weighted analyses suggest that this bias had a limited impact on our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support the updated guidelines, indicating that the introduction of food allergens should not be delayed and should occur “when CF is initiated any time after 4 months” 8 and “as early as the CF is initiated that is to say between 4 and 6 months” (updated French guidelines from the Public Health France website, September 2021) 36 . Recent studies underline the need for public health communications to disseminate and explain this change in the guidelines to parents and professionals who work with children 37,38 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it could be hypothesised that an increase in knowledge (as an intermediate outcome) could act as a proxy in changing behaviour. For example, a recent study has shown that providing child-feeding recommendations in paper format to parents can increase their knowledge accuracy and certainty regarding feeding recommendations (248) . As parents who are aware of the recommendations will not automatically align their feeding practices to what is recommended (249,250) , further investigation could clarify whether the knowledge of the recommendations triggers self-efficacy and could predict, ultimately, the adoption of optimal parental feeding practices and/or children's eating behaviours.…”
Section: Public Health Guidelines and Social Marketing To Promote Hea...mentioning
confidence: 99%